Smart Waste Management for Healthy Communities: Impactful Renewable Energy Innovations in Bekiung Village - Muhammadin Hamid; M Sabri; Nursal; Nazwa Armi; Hanafi Prayogo; Windy Indah Septia; Surayya Asyfha; Zahwan Asyrof Zahirul Ubaid (Talenta Publisher, 2025)
This community service program involves innovative waste management based on appropriate technology, utilizing the smart waste management concept, which processes agricultural and livestock waste into renewable energy sources such as organic fertilizer. The program was conducted in Bekiung Village, Kuala District, Langkat Regency, where cow dung and palm oil waste are the primary waste products. Through composting or co-composting, these two products can be converted into high-quality organic fertilizer that improves soil fertility. The core of the community service program is to create a community-based, sustainable waste management model that integrates simple technology, training, and mentoring. The goal is to reduce pollution, boost the local economy through waste-based industries, and support renewable energy and socio-ecological sustainability for the well-being of the village community.